Greek fragments in postmodern frames : rewriting tragedy 1970-2005 - Iōannidu, Eleutheria (Classical presences, 2017)
This text maps out the dialogue between Greek tragedy and major investigations of postmodern theory, focusing on adaptations produced between 1970 and 2005. Despite the large number of stage and script adaptations of the Greek tragic texts in this period, tragedy has been deemed to be incompatible with postmodernism